.9x-5.4=2.7(X+2)

Simple and best practice solution for .9x-5.4=2.7(X+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .9x-5.4=2.7(X+2) equation:


Simplifying
0.9x + -5.4 = 2.7(X + 2)

Reorder the terms:
-5.4 + 0.9x = 2.7(X + 2)

Reorder the terms:
-5.4 + 0.9x = 2.7(2 + X)
-5.4 + 0.9x = (2 * 2.7 + X * 2.7)
-5.4 + 0.9x = (5.4 + 2.7X)

Solving
-5.4 + 0.9x = 5.4 + 2.7X

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5.4' to each side of the equation.
-5.4 + 5.4 + 0.9x = 5.4 + 5.4 + 2.7X

Combine like terms: -5.4 + 5.4 = 0.0
0.0 + 0.9x = 5.4 + 5.4 + 2.7X
0.9x = 5.4 + 5.4 + 2.7X

Combine like terms: 5.4 + 5.4 = 10.8
0.9x = 10.8 + 2.7X

Divide each side by '0.9'.
x = 12 + 3X

Simplifying
x = 12 + 3X

See similar equations:

| 4/7b=-5/21 | | ab=(a+3b)(a-3b) | | x+3y+6=0 | | x-(x*0.075)=15.5 | | (1-v)(5v+7)=0 | | x-(x*0.15)=15.5 | | 6x-7=5x+3-2x | | 10x^2+10x-12=0 | | x-(4*.15)=15.5 | | 6-[6(-2+4)-4]= | | 3-2(5s+12)=21(s+2)-8s | | (x^2+4y+7)dx+(2x-y^3+1)dy=0 | | x+1-2=0 | | R/8=5 | | x-(x*0.3)=15.5 | | 2x-5y+21=0 | | 13(1/3) | | 3x-1/2=4x/5 | | -1+2(15-1)=h | | 2176/4[(5-1)^3-(4-)-5^3 | | 0.375w+2=w-1 | | 5x+1.2=8.2 | | 5x+2.2=8.2 | | 6x+15=2+(1-3x) | | 25=2/(.11-x) | | 2176/4[(5-1)3-(4-)-53 | | -3+6(19-1)=h | | 3+2(10-1)=z | | x(1.15)+40-x(0.85)=40 | | -8+5(14-1)=x | | x(1.15)+40-x(0.85)=1.00 | | x^2-2x+48= |

Equations solver categories